Left ventricular long-axis ultrasound strain (GLS) is an ideal indicator for patients with anti-hypertension treatment. (2nd January 2022) - Wu, Tingting; Zheng, Lulu; Zhang, Saidan; Duan, Lan; Ma, Jing; Zha, Lihuang; Li, Lingfang
ABSTRACT: Background: Primary hypertension is one of the most well-known risk factors for cardiovascular disease. Currently, there is still no ideal indicator for left ventricular end-diastolic pressure. Methods: 73 hypertension patients and 37 healthy people were enrolled in this study. Each member was examined with conventional echocardiography including multiple indicators such as Peak mitral valve flow velocity (E, A), E/A, left atrial volume index (LAVl), tissue Doppler (PW-TDI) peak velocities during early and late diastolic mitral valve flow (e '), E/e ', and GLS. We have collected clinical data from all enrolled members. The above cardiac ultrasound indicators were obtained before the antihypertensive treatment, one month and three months after treatment. Results: Left ventricular end-diastolic pressure (LVEDP) was positively correlated and negatively correlated with GLS (r = 0.638, P < .01) and E/e' (r = −0.578, P < .05), respectively. The hypertensives had lower e' value and higher values of GLS, E/e', and LAVI than the control group ( P < .05). GLS and E/e' were significantly lower in hypertension group than those in the Control group after one month and three months of treatment ( P < .05). The improvement rate of GLS was significantly higher than those in the improvement rate of e', E/e', LAVI after treatment ( p < .05). Conclusion: The GLS improvement rate was significantly higher than those of e', E/e' after one and three-month treatment. Therefore, GLS might be a potential ideal index for patients with anti-hypertension treatment. The results obtained in this study provide useful information for further study.